AGRESIVITAS MANUSIA DALAM MENEMPATI RUANG UNTUK PERMUKIMAN - Parfi Khadiyanto (Diponegoro University, 2012)
Human as economic being always strive to get opportunity to earn income by doing anything wherever it is. Human will seek for living place suitable for him in order to have living space to build settlement. There are two major options, that are to find comfortable place or place close to income source of the resultant of which one of the options will create the choice of living place suitable to him. Based on the two options; whether the choice for the close distance to the income source is more prominent rather than the needs for comfort. Industrial areas in Semarang is a location faces tide inundation, dense population, industrial pollution, and land subsidence, but the coming people is three times more than those leaving. The aim of this research is to figure out the ratio of human aggressiveness level to survive through income earning rather than to seek comfort and safety. The research uses descriptive qualitative method with correlation analysis. The result shows that the power to earn income has a great influence to ignore comfort and safety factor in selecting the location of the settlement.